The role of Ukrainian classical universities in formation of student’s culture of the safe life activity - Гвоздій, Світлана Петрівна (ScienceRise: Pedagogical Education, 2016)
There were analyzed the signs, functions, advantages, problems of classical universities in the system of higher education. There was demonstrated the condition of teaching the safe life activity in specialized, technical and classical HEI. There were given the regulatory documents that provide the process of teaching questions on civic safety in higher educational institutions of Ukraine. There are given reasons for possibilities of classical universities that prepare the wide spectrum of specialists of different specialties, for combination of mastering of humanitarian, natural, social, exact sciences with the process of formation of the safe life activity. There were offered the ways of structuring of the process of training the safety specialists. The defense and protection at emergencies and at productive activity is provided by graduates of technical and specialized higher educational institutions. Civic safety as a common safety of population, prophylactic work for guaranteeing the safety in everyday life and routine must be prerogative of graduates of classical universities. The preference in formation of culture of the safe life activity is given to the classical university. There is offered to use graduates of classical universities for realization of scientific, educational, volunteer and supporting role in safety provision